Long term outcome of adolescent and adult patients with pineal parenchymal tumors treated with fractionated radiotherapy between 1982 and 2003: a single institution's experience - Stoiber, Eva Maria; Schaible, Benjamin; Herfarth, Klaus; Schulz-Ertner, Daniela; Huber, Peter E.; Debus, Jürgen; Oertel, Susanne (Radiation oncology, 2010)
To evaluate the effectivity of fractionated radiotherapy in adolescent and adult patients with pineal parenchymal tumors (PPT).